2015
DOI: 10.1002/ijc.29857
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth and subsequent maternal risk of thyroid cancer

Abstract: Thyroid cancer has peak incidence among women of reproductive age, and growth factors, which have procarcinogenic properties, may play an important etiologic role. However, the association between fetal growth rate during a woman’s pregnancy and her subsequent risk of thyroid cancer has not been previously examined. We conducted a national cohort study of 1,837,634 mothers who had a total of 3,588,497 live-births in Sweden in 1973-2008, followed up for thyroid cancer incidence through 2009. There were 2,202 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Other placental hormones and growth factors that are increased during pregnancy may also contribute to thyroid cancer development. For instance, findings from a recent Swedish study showing an increased risk of maternal thyroid cancer associated with higher foetal growth and birthweight, support a possible role of placental IGF‐I . A history of infertility and use of fertility drugs have been associated with thyroid cancer risk in some studies , albeit not entirely consistently .…”
Section: Pregnancy Characteristics and Maternal Cancer Riskmentioning
confidence: 99%
“…Other placental hormones and growth factors that are increased during pregnancy may also contribute to thyroid cancer development. For instance, findings from a recent Swedish study showing an increased risk of maternal thyroid cancer associated with higher foetal growth and birthweight, support a possible role of placental IGF‐I . A history of infertility and use of fertility drugs have been associated with thyroid cancer risk in some studies , albeit not entirely consistently .…”
Section: Pregnancy Characteristics and Maternal Cancer Riskmentioning
confidence: 99%
“…Diagnosis of hyperemesis gravidarum has been associated with increased risk of maternal thyroid cancer (67). Higher fetal growth and birth weight also have been associated with an increased risk of maternal thyroid cancer (68), while longer duration of breastfeeding has been associated with a modest reduction in risk (65,69). It is not clear whether any or all of these findings are confounded by healthcare access or thyroid cancer screening, leading to the identification and diagnosis of subclinical thyroid cancers (63).…”
Section: Leukaemia/lymphoma Sarcomas and Other Solid Tumoursmentioning
confidence: 99%
“…3 However, other studies have shown that excessive fetal growth is associated with an increased risk of developing hormone-related cancers in mothers, such as breast, thyroid and ovarian cancer. [4][5][6] Moreover, a large cohort study in Sweden found that excessive fetal growth was independently associated with a higher risk of colorectal cancer. 7 The potential etiology of the different types of cancer may be the different in uences of rapidly increasing levels of estrogen, progesterone, insulin-like growth factor-1 (IGF-1), and leptin during pregnancy.…”
Section: Introductionmentioning
confidence: 99%